Sexual dimorphism, but not testosterone itself, is responsible for ankylosing enthesitis of the ankle in B10.BR (H-2k) male mice - Capkova, J; Ivanyi, P; Rehakova, Z (Annals of the rheumatic diseases, 2006)
BACKGROUND: Ankylosing enthesopathy (ANKENT) with progressive stiffening of ankle and tarsal joints of the hind limbs is a naturally occurring arthropathy in B10.BR mice. Some features are similar to those of the spondyloarthropathies in humans. OBJECTIVE: To study the role of sexual dimorphism and testosterone in the development of ANKENT. METHODS: The incidence of ANKENT was observed in non-castrated, castrated, and testosterone substituted castrated male mice, and in control and testosterone treated female mice. RESULTS: ANKENT occurred only in males; it did not develop in males castrated at age 2-3 months but occurred in castrated males injected with testosterone. Females injected with testosterone did not develop ANKENT. CONCLUSION: Testosterone can replace what castration eliminates, at least in the postpubertally castrated males, but is itself not sufficient to induce joint disease.
Keywords: Orchiectomy; Ankylosis; zadní končetina; myši inbrední C57BL; mužské pohlaví; Testosterone; Mice; ankylóza; orchiektomie; testosteron; ženské pohlaví; zvířata; Hindlimb; Humans; Sex Characteristics; myši; pohlavní dimorfismus; Female; Mice, Inbred C57BL; lidé; Male; Animals